2013
DOI: 10.3389/fncel.2013.00080
|View full text |Cite
|
Sign up to set email alerts
|

SCO-spondin from embryonic cerebrospinal fluid is required for neurogenesis during early brain development

Abstract: The central nervous system (CNS) develops from the neural tube, a hollow structure filled with embryonic cerebrospinal fluid (eCSF) and surrounded by neuroepithelial cells. Several lines of evidence suggest that the eCSF contains diffusible factors regulating the survival, proliferation, and differentiation of the neuroepithelium, although these factors are only beginning to be uncovered. One possible candidate as eCSF morphogenetic molecule is SCO-spondin, a large glycoprotein whose secretion by the diencepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 50 publications
3
45
1
5
Order By: Relevance
“…A majority of proteins found in the human and rat eCSF are secreted proteins which compose 27% and 33% of the total proteins found within the CSF, respectively [16]. Although it has also been demonstrated that the protein composition of embryonic CSF is more complex than that of adult CSF, our results indicate that adult CSF has the capacity to influence the behavior of adult NSCs in the adult brain, too [1,17,18]. The amount of protein in the CSF is low (normally < 0.5%) when compared to plasma, but the protein composition of this fluid is complex [3].…”
Section: Csf Componentsmentioning
confidence: 48%
See 2 more Smart Citations
“…A majority of proteins found in the human and rat eCSF are secreted proteins which compose 27% and 33% of the total proteins found within the CSF, respectively [16]. Although it has also been demonstrated that the protein composition of embryonic CSF is more complex than that of adult CSF, our results indicate that adult CSF has the capacity to influence the behavior of adult NSCs in the adult brain, too [1,17,18]. The amount of protein in the CSF is low (normally < 0.5%) when compared to plasma, but the protein composition of this fluid is complex [3].…”
Section: Csf Componentsmentioning
confidence: 48%
“…The central nervous system (CNS) develops from the neural tube, a hollow structure filled with embryonic cerebrospinal fluid (eCSF) and surrounded by neuroepithelial cells. Several evidence suggest that the eCSF contains diffusible factors such as transforming growth factor-ß (TGF-ß), nerve growth factor (NGF), brain derived neurotrophic factor (BDNF), neurotrophin-3 (NT-3), insulin-like growth factor (IGF), and hepatocyte growth factor (HGF), regulating the survival, proliferation, and differentiation of the neuroepithelium [1]. CSF is a vital signaling system involved in the development of the cerebral cortex and probably also the rest of CNS [2].…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is the ability to produce and secrete a glycoprotein called subcomissural organ (SCO)‐spondin (also known as Reissner’s substance). This substance has been implicated in a multitude of functions, including modulation of cell adhesion, migration, neuronal survival, differentiation, axonal growth, CNS morphogenesis, and facilitation of the cerebrospinal fluid flow (Meiniel, ; Huh et al , ; Vera et al , ). In vertebrate embryos, SCO‐spondin is transiently produced by the radial glia of the floor plate during CNS development.…”
Section: Radial Glia In Echinodermsmentioning
confidence: 99%
“…These will eventually generate all the neurons and glial cells of the cerebral cortex together with the median and lateral eminence that provide post-natal neurogenesis and cortical interneurons (reviewed in (1,2). The neural tube and cephalic vesicles are filled with embryonic cerebrospinal fluid (E-CSF) which plays important roles in neural development at both embryonic and fetal stages, regulating the survival, proliferation, and neural differentiation of the neuroepithelial progenitor cells (3)(4)(5).At the start of the major phase of cortical development, high volume CSF is secreted by the ventricular choroid plexus (6). The generation of neurons and glia from proliferating neural progenitor/stem cells is a complex process (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%